Applying comsol multiphysics for research and development of capacitive pressure sensor - Marikutsa, U.; Narushynska, О.; Medvid, A. (Видавництво Львівської політехніки, 2015)
Спроектовано та досліджено моделі давача тиску ємнісного типу в середовищі Comsol. Застосовано алгоритм побудови моделі за допомогою пакета Comsol. Article contains design and researching of capacitive pressure sensor's model in the Comsol environment. Model constructing algorithm applied by using Comsol package.
Keywords: ємнісний давач тиску; конденсатор; чутливий елемент; COMSOL Multiphysics; система автоматизованого проектування; МЕМС –мікроелектромеханічні системи; capacitive pressure sensor; capacitor; sensor; COMSOL Multiphysics; сomputeraided design; MEMS – Microelectromechanical systems